Serum and aqueous humor adiponectin levels correlate with diabetic retinopathy development and progression - Yang, Hyun Seung; Choi, Young Je; Han, Hee Yong; Kim, Hak Su; Park, So Hyun; Lee, Kyung Sub; Lim, Sang Hwa; Heo, Doo Jin; Choi, Sangkyung (PloS one, 2021)
To compare adiponectin (APN) levels in the serum and aqueous humor (AH) and evaluate their association with the development/progression of diabetic retinopathy (DR). Diabetic patients with (group 3; n = 59) and without (group 2; n = 39) DR and age- and sex-matched normal subjects (group 1; n = 35) were compared. Duration of diabetes, body mass index, serum HbA1c, vascular endothelial growth factor (VEGF), APN, pentraxin 3 (PTX3), platelet derived growth factor (PDGF), intercellular adhesion molecule-1 (ICAM-1), and APN were measured and analyzed. One hundred and thirty-three participants were included. Compared to patients without diabetes, diabetic patients with DR had significantly elevated average serum APN levels (5.99±3.89 μg/ml versus 3.51±1.44 μg/ml, P = 0.002) and average AH APN levels (10.94±11.74 ng/ml versus 3.65±3.33 ng/ml, P<0.001). Serum APN was significantly correlated with AH APN (R = 0.512, P<0.001) and AH VEGF (R = 0.202, P = 0.020). The log serum APN was significantly correlated with intraocular cytokines, including log APN, log VEGF, log ICAM, log leptin, log PTX3, log PDGF, angiopoietin, C-reactive protein, and interleukins (IL)-5 and IL-10 (P<0.001, P = 0.020, P<0.001, P<0.001, P = 0.001, P<0.001, P = 0.008, P = 0.009, P<0.001, and P = 0.046, respectively). Log serum VEGF showed a significant correlation only with log AH VEGF (P = 0.001). Multivariate logistic analysis was performed to evaluate the association of DR progression and cytokine concentrations; log Serum APN and log AH APN showed good correlation with the DR progression in each model. AH APN levels correlated well with DR development and progression. Serum APN could be a better marker for estimating intraocular cytokines, including both intraocular APN and VEGF concentrations in clinical field, than serum VEGF in DR patients.